If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -1(3x + 7) = 4x + -10 Reorder the terms: 6x + -1(7 + 3x) = 4x + -10 6x + (7 * -1 + 3x * -1) = 4x + -10 6x + (-7 + -3x) = 4x + -10 Reorder the terms: -7 + 6x + -3x = 4x + -10 Combine like terms: 6x + -3x = 3x -7 + 3x = 4x + -10 Reorder the terms: -7 + 3x = -10 + 4x Solving -7 + 3x = -10 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -7 + 3x + -4x = -10 + 4x + -4x Combine like terms: 3x + -4x = -1x -7 + -1x = -10 + 4x + -4x Combine like terms: 4x + -4x = 0 -7 + -1x = -10 + 0 -7 + -1x = -10 Add '7' to each side of the equation. -7 + 7 + -1x = -10 + 7 Combine like terms: -7 + 7 = 0 0 + -1x = -10 + 7 -1x = -10 + 7 Combine like terms: -10 + 7 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3
| 5=(-2x)+3x | | -3y=471 | | -32=3x+10 | | -106+2x=92-7x | | R^2+12=7R | | 12d=5*5 | | 28=4u-16 | | 11g-2g-12g=-39 | | d/10-1=-31 | | (4x+1)-(6x-5)= | | 9s=8*36 | | 136=-8(1+3a) | | 8n-(5n+4)=14 | | 19s+60=31-s | | 5[4(2m+n+3)-6m-1]+2(5m-n)= | | -8y-(x-4x)+3= | | 3x-150=-39 | | -7(k+3)-4k=-109 | | 3(x-8)=2(x+3) | | 5a-16-8a=-10 | | 4x+1.18=-3.1(2-.01x) | | 2g+3(-8+3G)=1-g | | (-10)=6+4x-6x | | 31-(2c+4)=2(c+6)+c | | 722=485+b | | (5s-2t)-(2s-4t)= | | 7a=36*21 | | X+59+84+X+51=180 | | 128=-8(-2+2p) | | 42p-39=66p-87 | | 7-3d-5=-1+2d-12+d | | 247=-7(-1+8b)-4b |